Nurses and implementation of the Nursing Process: descriptive study - Azeredo, Lidiane Grutzmacher; Silva, Rosângela Marion da; Lima, Ana Amélia Antunes (Online Brazilian Journal of Nursing, 2010)
The following descriptive study aimed to identify the benefits and difficulties the implementation of the Nursing Care Systematization. The collection of data happened from September to October 2008 applying a survey to 16 nurses. The data were submitted to descriptive statistics. The results showed in relation to benefits: quality of the patient assistance, the organization of the nursing assistance and definition and appreciation of the role of nurses.The doubts for the execution of implementation were resolubility and lack of time. These results reveal that is possible to promote better management of the nursing assistance through it. This can happen since the organization of the nursing assistance from which the nurser is responsible for enables the quality of the service offered to the patient.